Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

While working on a differential equation I stumbled on this integral: $$\int_0^x\frac{e^{-t^2}}{a^2+t^2}dt,$$ where $a\in \mathbb{R_{>0}}$.

At first glance it looks so simple that it's ridiculous that I can't find closed form expression for it.

Can someone help me with this beast?

$Edit:$From the comments, it doesn't seem to exist a closed form. I tried a series expansion by writing the integrand as $e^{-t^2}g(t)$ and take the Taylor expansion of the function $g(t)$. It's a good approximation and it's possible to integrate the expression found but it's only valid for small values of $x$ since the series diverge.

share|improve this question
    
I'm not sure it has a closed expression. Try to exchange the integrals, hopefully the other direction gets you some $t$ as multiplier. –  Berci Jun 13 '13 at 23:25
    
Or, perhaps, do you want its limit as $x\to\infty$? –  Berci Jun 13 '13 at 23:27
    
@Berci Well, there's no other integration to be made. I have a ODE whose solution is $f(x)=\int_0^x \frac{e^{-t^2}}{a^2+t^2}dt+...$. So I can't take the limit. I'm sorry if I misled you with the way I wrote the question. –  PML Jun 13 '13 at 23:32
    
I would guess that this does not have an expression in terms of elementary functions. –  par Jun 13 '13 at 23:33
1  
@par I wasn't implying that it does. I was just answering the first two comments. –  PML Jun 13 '13 at 23:36

2 Answers 2

up vote 11 down vote accepted

$\int_0^x\dfrac{e^{-t^2}}{a^2+t^2}dt=\int_0^x\dfrac{1}{a^2+t^2}\sum\limits_{n=0}^\infty\dfrac{(-t^2)^n}{n!}dt=\int_0^x\sum\limits_{n=0}^\infty\dfrac{(-1)^nt^{2n}}{n!(a^2+t^2)}dt$

Consider $\int\dfrac{t^{2n}}{a^2+t^2}dt$ ,

Let $t=a\tan\theta$ ,

Then $dt=a\sec^2\theta~d\theta$

$\therefore\int\dfrac{t^{2n}}{a^2+t^2}dt$

$=\int\dfrac{(a\tan\theta)^{2n}}{a^2+(a\tan\theta)^2}a\sec^2\theta~d\theta$

$=\int a^{2n-1}\tan^{2n}\theta~d\theta$

$=\sum\limits_{k=0}^{n-1}\dfrac{(-1)^ka^{2n-1}\tan^{2n-2k-1}\theta}{2n-2k-1}+(-1)^na^{2n-1}\theta+C$

$=\sum\limits_{k=0}^{n-1}\dfrac{(-1)^ka^{2k}t^{2n-2k-1}}{2n-2k-1}+(-1)^na^{2n-1}\tan^{-1}\dfrac{t}{a}+C$

Hence $\int_0^x\sum\limits_{n=0}^\infty\dfrac{(-1)^nt^{2n}}{n!(a^2+t^2)}dt$

$=\left[\sum\limits_{n=1}^\infty\sum\limits_{k=0}^{n-1}\dfrac{(-1)^{n+k}a^{2k}t^{2n-2k-1}}{n!(2n-2k-1)}+\sum\limits_{n=0}^\infty\dfrac{a^{2n-1}}{n!}\tan^{-1}\dfrac{t}{a}\right]_0^x$

$=\sum\limits_{n=1}^\infty\sum\limits_{k=0}^{n-1}\dfrac{(-1)^{n+k}a^{2k}x^{2n-2k-1}}{n!(2n-2k-1)}+\dfrac{e^{a^2}}{a}\tan^{-1}\dfrac{x}{a}$

share|improve this answer
    
This is outstanding!Thank you very much, really. I hope you get many upvotes for the work you've put into this answer. Thank you once again. –  PML Jun 15 '13 at 0:50

I'll tackle the case of the large values of $x$. Let's express the integral as follows:

$$\int_0^x\frac{e^{-t^2}}{a^2+t^2}dt=\int_0^{\infty}\frac{e^{-t^2}}{a^2+t^2}dt-\int_x^{\infty}\frac{e^{-t^2}}{a^2+t^2}dt=$$

$$=I(a)-\int_x^{\infty}\frac{e^{-t^2}}{a^2+t^2}dt$$

The next step is evaluate the last integral by parts:

$$-\int_x^{\infty}\frac{e^{-t^2}}{a^2+t^2}dt=\frac{1}{2}\int_x^{\infty}\frac{d(e^{-t^2})}{t(a^2+t^2)}dt=$$

$$=-\frac{e^{-x^2}}{2x(a^2+x^2)}+\frac{1}{2}\int_x^{\infty}\frac{(3t^2+a^2)e^{-t^2}}{t^2(a^2+t^2)^2}dt$$

In the last expression, the first term dominates for large $x$ and we have approximately:

$$\int_0^x\frac{e^{-t^2}}{a^2+t^2}dt\approx I(a)-\frac{e^{-x^2}}{2x(a^2+x^2)}$$

We'll get a better result if we continue the integration by parts in the penultimate expression.

Now, consider

$$I(a)=\int_0^{\infty}\frac{e^{-t^2}}{a^2+t^2}dt$$

Let's introduce the parameter $b$ so that

$$J(b)=\int_0^{\infty}\frac{e^{-bt^2}}{a^2+t^2}dt$$

and $I(a)=J(1)$

By differentiating with respect to $b$ we will see that $J$ satisfies the following differential equation:

$$\frac{dJ}{db}-a^2J+\frac{\sqrt{\pi}}{2\sqrt{b}}=0$$

Taking into account that

$$J(0)=\int_0^{\infty}\frac{dt}{a^2+t^2}=\frac{\pi}{2a}$$ we get a solution of this diff-eq:

$$J(b)=\sqrt{\pi}\frac{e^{a^2b}}{a}\int_{a\sqrt{b}}^{\infty}e^{-y^2}dy$$

Finally

$$I(a)=J(1)=\sqrt{\pi}\frac{e^{a^2}}{a}\int_{a}^{\infty}e^{-y^2}dy=\frac{\pi}{2}\frac{e^{a^2}}{a}\text{erfc}(a)$$ where $\text{erfc}(x)=\frac{2}{\sqrt{\pi}}\int_{x}^{\infty}e^{-y^2}dy$ is so called "the complementary error function"

share|improve this answer
    
I'm learning a lot with your answers. I thank you very much with the time you took on your answer. Your approach is very interesting and pedagogical. Thank you once again –  PML Jun 17 '13 at 21:12

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.